Factors that affect the nearshore aggregations of Antarctic krill in a biological hotspot. (August 2017) - Bernard, Kim S.; Cimino, Megan; Fraser, William; Kohut, Josh; Oliver, Matthew J.; Patterson-Fraser, Donna; Schofield, Oscar M.E.; Statscewich, Hank; Steinberg, Deborah K.; Winsor, Peter
Abstract: Antarctic krill, Euphausia superba, is a highly abundant and ecologically important zooplankton species in the Southern Ocean. Regions of elevated Antarctic krill biomass exist around Antarctica, often as a result of the concentrating effect of bathymetry and ocean currents. Such areas are considered biological hotspots and are key foraging grounds for numerous top predators in the region. A hotspot of Antarctic krill biomass exists off the southern extent of Anvers Island, Western Antarctic Peninsula, and supports a population of Adélie penguins that feed almost exclusively on it, as well as numerous other top predators. We investigated the spatio-temporal variability in Antarctic krill biomass and aggregation structure over four consecutive summer seasons, identifying environmental factors that were responsible. We identified three distinct krill aggregation types (Large-dense, Small-close and Small-sparse), and found that the relative proportion of each type to total aggregation numbers varied significantly between survey days. Large-dense aggregations occurred more frequently when westerly winds predominated and when the local mixed tide was in the diurnal regime. Small-close aggregations were also more frequent during diurnal tides and were negatively correlated with phytoplankton biomass. Small-sparse aggregations, on the other hand, were more prevalent when the mixed tide was in the semi-diurnal phase. We suggest that, under certain conditions (i.e. diurnal tides and westerly winds), the biological hotspot in the nearshore waters off Palmer Station, Anvers Island, functions as a zone of accumulation, concentrating krill biomass. Our findings provide important information on the dynamics of Antarctic krill at the local scale. Highlights: Variability in Antarctic krill aggregations was assessed in a biological hotspot. Large, dense krill aggregations are more frequent during diurnal tides and westerly winds. The biological hotspot off Palmer Station functions as a zone of accumulation.